Facilitation or inhibition? Impact of CEO’s financial background on industrial AI transformation of manufacturing companies - Xu, Peng; Zhang, Zichao (Frontiers in Psychology, 2023)
Introduction The purpose of this paper is to empirically test the impact of CEO’s financial background on industrial AI transformation of manufacturing enterprises based on upper echelons theory and imprinting theory. Methods The paper preliminarily takes listed manufacturing companies in Shanghai and Shenzhen stock markets that are affiliated to enterprise groups from 2014 to 2020 as samples, and manually collects and collates datas of CEO’s financial background and industrial AI transformation. The research hypotheses are tested by stata 15.0 software. Results It is found that CEO’s financial background significantly inhibits the industrial AI transformation of manufacturing enterprises, and when the CEO works part-time in the parent company, it will strengthen the negative impact of CEO’s financial background on industrial AI transformation. Further research shows that enterprise financialization plays a partial intermediary role between CEO’s financial background and industrial AI transformation; Compared with private enterprise groups, the inhibiting effect of CEO financial background on industrial AI transformation is stronger in state-owned enterprise groups; CEOs with non-banking financial background have a stronger inhibitory effect on industrial AI transformation. Discussion Firstly, based on the process of making business decisions, it verifies and clarifies the action mechanism of CEO’s financial background on industrial AI transformation through internal driving mechanism, which expands the research horizon of industrial AI transformation, and further applies the Imprinting Theory in biology to the research of business decision-making, which forms a beneficial complement to the relevant research on economic consequences of CEO’s financial background. Secondly, different from the research of single independent company, this paper focuses on the special situation of parent-subsidiary corporate governance, and explores the mechanism of action, deepening the research on the synergy of enterprise groups. Finally, this paper further explores the influence of CEO’s financial background on industrial AI transformation, which is conducive to a deeper understanding of the heterogeneity of managers except manpower and capital factors in the industrial AI transformation practice of manufacturing enterprises, and provides a new idea and a more comprehensive analysis perspective for industrial AI transformation.